Hungarian Monitoring, 17 November 1989 . [Magyar rádiófigyelő], 1989. november 17 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Mass demonstration in Prague - Parliament in session in Berlin - Report on Bulgarian parliament in session - Gorbachev on modifying the constitution - Ryzhkov receives striking miners from Vorkuta - Shevardnadze's speech - Introducing the new government of the GDR Domestic Affairs: - Hungarian Socialist Party (MSZP) on the referendum - Planned restoration of the Danube bed begins at Nagymaros - 21-member Israeli delegation in Hungary - Hungarian Democratic Forum (MDF) after its party congress - Romanian refugees Economy: - Readiness to strike at Rába Factory - Two Common Market leaders in talks in Budapest Külpolitika: - Tömegtüntetés volt Prágában - Ülésezik a parlament Berlinben - Beszámoló a bolgár parlament üléséről - Gorbacsov az alkotmánymódosításról - Rizskov fogadta a sztrájkoló vorkutai bányászokat - Sevardnadze beszéde - Bemutatták az NDK új kormányát Belpolitika: - Az MSZP a népszavazásról - Nagymarosnál megkezdődött a Duna-meder helyreállításának előkészítése - Huszonnégy tagú izraeli delegáció járt hazánkban - Kongresszus után az MDF - Romániai menekültügy Gazdaság: - Sztrájkkészültség a Rába Gyárnál - Budapesten tárgyalt a Közös Piac két vezetője